Questionnaires in Second Language Research: Construction, Administration, and Processing By Zoltán Dörnyei and Jean-Marc Dewaele - Mohamadi, Samira; Aghayani, Behnam (LEARN Journal: Language Education and Acquisition Research Network, 2024)
Questionnaires constitute an essential part of conducting quantitative or mixed-methods research. Despite their seemingly straightforward nature, the use of questionnaires requires adequate knowledge and skill. However, many researchers, particularly novice individuals, often lack sufficient information regarding developing, administrating, and processing questionnaires in conducting their research.